Temporal Changes in Individualism and Their Ramification in Japan: Rising Individualism and Conflicts with Persisting Collectivism - Ogihara, Yuji (Frontiers in Psychology, 2017)
Many studies have shown that American culture has become more individualistic over time. However, it was unclear whether other cultures, especially East Asian cultures, have also shifted toward greater individualism. Therefore, this article reviewed studies investigating temporal changes in individualism in Japan and their ramifications on psychology and behavior. Japan has experienced rapid and dramatic economic growth and urbanization and has adopted more social systems based on individualistic concepts in various contexts (e.g., workplace, school). Recent studies have suggested that, along with these socioeconomic changes, Japanese culture has become more individualistic over time. Specifically, the divorce rate increased and household size decreased. Moreover, people give more unique names to their children and dogs, and individualistic words such as “individual” and “uniqueness” appear more frequently in newspapers. Furthermore, social values became more individualistic. Yet, it has also been shown that some collectivistic values still remain. As a result, people have difficulty in adapting to this coexistence, which injures interpersonal relationships and well-being. This paper discussed how Japanese culture changed over time and how such changes affected Japanese psychology and behavior.